Soil gas and solute diffusivity as predictors of N2O emissions after spring fertilization: An incubation study with intact soil - Winnie Ntinyari; Loraine ten Damme; Jianbo Cheng; Lars J. Munkholm; Søren O. Petersen (Geoderma)
Agricultural soils are the main source of anthropogenic N2O emissions to the atmosphere. To effectively mitigate these emissions there is a need to understand the interactions between potential drivers under field conditions. We conducted an incubation experiment with intact soil cores adjusted to one of four matric potentials (−15, −30, −50 or −100 hPa). We measured the relative gas diffusivity (Dp/Do) and effective air-filled porosity (εeff) before incubation with four surface-applied fertiliser treatments: NS26-13 (NS) at 50 kg N ha−1 (NS50; starter); NS at 50 + 100 kg N ha−1 (NS150); NS at 50 + 100 kg N ha−1, the main dose of 100 kg N ha−1 containing the nitrification inhibitor 3,4-dimethylpyrazol phosphate (NS150 + DMPP); and an unfertilized Control. We monitored N2O fluxes for 35 days and found a positive relationship with matric potential and a weak inverse relationship with Dp/Do and εeff.. After 35 days, the cores were sectioned for determination of mineral N pools and potential ammonia oxidation (PAO). A strong NH4+ gradient, declining with depth, was observed which indicated that nitrification took place at some distance from the surface-applied fertiliser, and this was consistent with PAO and pH distributions. The flux of NH4+ in the soil solution between 0–2 and 2–4 cm depth after 35 days showed a consistent relationship with N2O emissions at −30 to −100 hPa indicating nitrification was the main source of N2O in this range. The results of this study suggest that both gas and solute diffusivity have to be considered for predicting N2O emissions from surface-applied fertilisers.